In vitro recapitulation of the site‐specific editing (to wild‐type) of mutant IDS mRNA transcripts, and the characterization of IDS protein translated from the edited mRNAs. Issue 7 (22nd May 2017) - Lualdi, Susanna; Del Zotto, Genny; Zegarra‐Moran, Olga; Pedemonte, Nicoletta; Corsolini, Fabio; Bruschi, Maurizio; Tomati, Valeria; Amico, Giulia; Candiano, Giovanni; Dardis, Andrea; Cooper, David N.; Filocamo, Mirella
Abstract : The transfer of genomic information to the primary RNA can be altered by RNA‐editing. In three Hunter syndrome patients, we have shown that IDS genomic variants can be RNA‐edited to wild‐type. An in vitro system employing different cell types was established to recapitulate, and hence confirm, the site‐specific editing of IDS RNA observed ex vivo in the three patients. Confocal microscopy, flow cytometry and confocal high‐content analyses demonstrated the expression and lysosomal localization of GFP‐labeled‐proteins translated from edited IDS mRNAs. Abstract: The transfer of genomic information into the primary RNA sequence can be altered by RNA editing. We have previously shown that genomic variants can be RNA‐edited to wild‐type. The presence of distinct "edited" iduronate 2‐sulfatase ( IDS ) mRNA transcripts ex vivo evidenced the correction of a nonsense and frameshift variant, respectively, in three unrelated Hunter syndrome patients. This phenomenon was confirmed in various patient samples by a variety of techniques, and was quantified by single‐nucleotide primer extension. Western blotting also confirmed the presence of IDS protein similar in size to the wild‐type. Since preliminary experimental evidence suggested that the "corrected" IDS proteins produced by the patients were similar in molecular weight and net charge to their wild‐type counterparts, an in vitro system employing different cell types was established to recapitulate the site‐specific editing of IDS RNA (uridine to cytidine conversion and uridine deletion), and to confirm the findings previously observed ex vivo in the three patients. In addition, confocal microscopy and flow cytometry analyses demonstrated the expression and lysosomal localization in HEK293 cells of GFP‐labeled proteins translated from edited IDS mRNAs. Confocal high‐content analysis of the two patients' cells expressing wild‐type or mutated IDS confirmed lysosomal localization and showed no accumulation in the Golgi or early endosomes.